Activatable Chemiluminescent Molecular Probes for Bioimaging and Biosensing. Issue 2 (26th January 2021) - Yang, Yanling; Zhang, Fan
Abstract: Chemiluminescence (CL) is a very promising method for applications in analytic chemistry and biological systems due to the elimination of the external light source, which could reduce autofluorescence interference and improve the signal‐to‐noise ratio (SNR) and tissue penetration depth. The fluorescent dyes, chemiluminescent initiator, and reaction temperature are three crucial factors that determine the chemiluminescence efficiency. Up to now, significant development of chemiluminescence probes has been reported for high‐performance imaging and sensing, including the systems based on luminol, imidazopyrazinone, peroxyoxalate, and Schaap's dioxetane. In this review, we give an overview of the current chemiluminescence probes and their bioimaging and biosensing applications. We also provide perspectives on designing chemiluminescent probes with good efficiency and longer emission wavelengths. Abstract : Chemiluminescence (CL) presents the major advantages of reduced autofluorescence interference, improved signal‐to‐noise ratio (SNR) and deeper tissue penetration. CL systems based on luminol, imidazopyrazinone, peroxyoxalate and Schaap's dioxetane occupy a central position in bioimaging and biosensing. In this review, strategies for designing chemiluminescence probes with good efficiency and longer emission wavelength are discussed.